Liquid metal embrittlement and deformation induced martensite: The case of 316 L austenitic steel LME by liquid eutectic gallium-indium. (November 2021) - Auger, T.; Michel, V.; Cassayre, L.; Baketi, H.; Barkia, B.; Michel, A.; Perrin, E.
Abstract: The liquid metal embrittlement sensitivity of a low nickel 316 L austenitic steel has been studied with eutectic gallium indium alloy. The embrittlement case is firmly established with this steel and studied by X-Ray fractography and EBSD. Brittle to ductile recoveries were observed via a dedicated parametric study (varying cross-head speed and temperature). The return to ductility with temperature is strongly correlated with a significant reduction in plastically induced α' phase change suggesting it is a requirement for LME. This implies a strategy focused on limiting deformation induced martensite to design LME resistant austenitic steels at low temperature. Highlights: Liquid Metal Embrittlement (LME) of the 316 L austenitic steel is studied as a function of temperature and strain rate. LME is found from room temperature up to 50 °C. A ductile recovery is observed above. LME is observed at low strain rate. X-Ray fractography quantified the amount of γ to α' martensitic phase transform induced by plastic deformation (DIM). A strong correlation (p value < 0.0067) is observed between LME of stainless steel and DIM.